Isolation of a Reactive Black-5-decolourizing Fungus, Absidia californica MT-1, from cement-Contained Soil and the Optimization of Culture Conditions for Dye Removal - Taskin, Mesut; Erdal, Serkan (Asian Journal of Chemistry, 2010)
The present study focused on the removal of textile dye Reactive Black-5 by actively growing mycelia of fungus Absidia californica MT-1, which was isolated from the cement-contamined soil. The temperature of 28 ºC, shaking speed of 180 rpm, pH 5, inoculum amount of 0.2 g/L, 15 g/L sucrose and 1 g/L ammonium chloride were the most efficient conditions to achieve optimum removal of dye. Nutrient-poor medium was found to be more beneficial for dye removal. Biosorption/bioadsorption was likely the dominant mechanism for dye removal by the fungus and found to be associated with mycelial morpholgy. The mycelial morphology in small uniform pellet form was found to be better for dye removal. The maximum dye removal by A. californica MT-1 was 92 % (0.276 g/L bioadsorbed-dye) with 3.95 g/L of biomass production at an initial dye concentration of 0.3 g/L in 108 h. In the present study, both the ability of this fungus species to remove a textile dye and the usability of cement-contamined soil as a source of microorganisms, which are capable of removing snythetic textile dye, were investigated for the first time.